Concordance and Discordance of Self-Rated and Researcher-Measured Successful Aging: Subtypes and Associated Factors. (1st March 2017) - Gu, Danan; Feng, Qiushi; Sautter, Jessica M.; Yang, Fang; Ma, Lei; Zhen, Zhihong
Abstract: Objectives: To investigate subtypes of successful aging (SA) based on concordance and discordance between self-rated and researcher-defined measures and their associations with demographic, psychosocial, and life satisfaction factors. Method: We used multinomial logistic regression models to analyze 2013 cross-sectional survey data from 1, 962 persons aged 65 and older in Shanghai that measured self-rated successful aging (SSA) with a single global assessment and researcher-defined successful aging (RSA) with a cumulative deficit index reflecting physical, physiological, cognitive, psychological, and social engagement domains. We generated four subtypes based on these two dichotomous variables: nonsuccessful aging (non-SA; meeting neither the criterion of RSA nor the criterion of SSA), RSA-only (meeting the criterion of RSA-only but not the criterion of SSA), SSA-only (meeting the criterion of SSA-only but not the criterion of RSA), and both-successful aging (both-SA; meeting both criteria of RSA and SSA). Results: In the sample, 32% were nonsuccessful agers, 7% RSA-only, 34% SSA-only, and 27% successful agers. Female gender and older age were associated with lower likelihood of RSA-only and both-SA relative to non-SA, but with greater likelihood of SSA-only. Good socioeconomic conditions and social networks were associated with greater likelihood of SSA-only and both-SA relative to non-SA or RSA-only. Satisfaction with life domains was robustly and positively associated with good successful aging outcomes. Discussion: Researcher-defined successful aging and self-rated successful aging are different measures with distinct social correlates. Subtypes of concordance and discordance provide a more holistic biopsychosocial conceptualization of successful aging.